Compression-resistant high-temperature-resistant easy-heat-dissipation new energy automobile charging cable

By adding modified additives and hyperbranched flame retardants to the outer sheath layer of new energy vehicle charging cables, the problems of fire risk and insufficient material performance of charging cables in high temperature environments are solved, and excellent mechanical properties, resistance and resistance are achieved. combustion performance, thermal oxygen aging resistance and thermal conductivity.

CN119314736AActive Publication Date: 2025-01-14GUANG DONG LI GUANG DIAN QI SHI YE YOU XIAN GONG SI

Patent Information

Application Number
CN202411461755.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-14
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Existing new energy vehicle charging cables are prone to fire in high temperature environments, and the materials have insufficient flame retardant properties, mechanical properties and thermal oxygen aging resistance, which are difficult to meet the needs of compressive resistance and heat dissipation.

Method used

By adding modified additives and hyperbranched flame retardants to the outer sheath layer, the mechanical properties, flame retardant properties, thermal oxygen aging resistance and thermal conductivity of the material are improved. The modified additive enhances the mechanical properties and thermal conductivity of the material through the grafting reaction of ammonium polyphosphate and graphene oxide; the hyperbranched flame retardant improves the flame retardant properties and maintains them through the connection of DOPO derivatives and phosphorus oxychloride. Mechanical properties of materials.

Benefits of technology

It achieves the excellent mechanical properties, flame retardant properties, thermal oxygen aging resistance and thermal conductivity of the charging cable, and improves the safety and service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314736A_ABST
    Figure CN119314736A_ABST
Patent Text Reader

Abstract

The invention relates to the field of cables, and discloses a compression-resistant high-temperature-resistant easy-heat-dissipation new energy automobile charging cable, which sequentially comprises a belting layer, a copper wire braided total shielding layer and an outer sheath layer from inside to outside, and is characterized in that three power wire cores, a ground wire cable core, two signal control wire cores and two auxiliary power wire cores are arranged in the belting layer; each power wire core comprises a conductor and an insulating layer extruded on the outer surface of the conductor, and the outer sheath layer comprises the following raw materials in parts by weight: 70-90 parts of PVC resin, 20-30 parts of a polyurethane thermoplastic elastomer, 10-15 parts of a modified additive, 2-5 parts of a hyperbranched flame retardant, 5-10 parts of a plasticizer, 4-7 parts of a stabilizer and 1-3 parts of a lubricant. The material is endowed with excellent mechanical properties, flame retardancy, thermo-oxidative aging resistance and heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cables, and in particular relates to a pressure-resistant, high-temperature-resistant and easy-to-dissipate heat dissipation new energy vehicle charging cable. Background Art

[0002] New energy vehicles refer to vehicles that use unconventional automotive fuels as their power source (or use conventional automotive fuels and adopt new on-board power devices), and integrate advanced technologies in vehicle power control and drive. The resulting vehicles have advanced technical principles, new technologies, and new structures. They can effectively reduce pollution to the environment, save energy, and be environmentally friendly. They have received support from various countries and regions, and not only have the new energy vehicle industry been developed on a large scale, but supporting charging piles and charging stations have also been widely built and put into operation.

[0003] When existing new energy vehicles are charged, fires often occur due to the long charging time. Therefore, the charging cables used must have good high temperature resistance and flame retardant effects. In order to improve the flame retardant properties of cable materials, the existing technology often adds a large amount of inorganic flame retardants. The currently commonly used small molecule flame retardants mainly include: halogen-containing flame retardants, phosphorus-based flame retardants, silicon-based flame retardants, nitrogen-based flame retardants and composite flame retardants. Due to the poor compatibility of small molecule flame retardants with materials, the mechanical properties of materials will be reduced, and the viscosity, compatibility and flexibility of polymer materials will also be deteriorated. In addition, there are many cars coming and going in the charging occasions, and the cables need to have excellent compression resistance. At the same time, the charging pile cables are frequently dragged and exposed to the outdoor environment for a long time during use, and the load current value is relatively large. The heat generated by the high current can easily cause the cable materials to heat up and age. Therefore, the charging cable materials should have good heat and oxygen aging resistance and good mechanical properties. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a pressure-resistant, high-temperature-resistant and easy-to-dissipate heat dissipation new energy vehicle charging cable. By adding modified additives and hyperbranched flame retardants, the sheath layer material is endowed with excellent mechanical properties, flame retardant properties, heat-resistant oxygen aging properties and heat resistance.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable, the charging cable comprising, from the inside to the outside, a tape layer, a copper wire braided total shielding layer, and an outer sheath layer, the tape layer is provided with three power cores, one ground cable core, two signal control cores, and two auxiliary power cores, the power core comprises a conductor and an insulating layer extruded on the outer surface of the conductor, the signal control core is provided with two signal cores, the outer surface of the signal core is sequentially coated with an aluminum-plastic composite tape shielding layer and a copper wire braided shielding layer, and the gaps between the tape layer and the three power cores, one ground cable core, two signal control cores, and two auxiliary power cores are filled with a filling layer;

[0007] The outer sheath layer comprises the following raw materials in parts by weight: 70-90 parts of PVC resin, 20-30 parts of polyurethane thermoplastic elastomer, 10-15 parts of modified additives, 2-5 parts of hyperbranched flame retardant, 5-10 parts of plasticizer, 4-7 parts of stabilizer, and 1-3 parts of lubricant;

[0008] The modified additive is prepared by gamma-glycidyloxypropyltrimethoxysilane treated silicon dioxide coated with ammonium polyphosphate grafted with amination graphene oxide and then further grafted with amination boron nitride nanosheets; the hyperbranched flame retardant is prepared by using DOPO, terephthalaldehyde and 1,5-naphthalenediamine as raw materials to synthesize DOPO derivatives and then using phosphorus oxychloride as a linker.

[0009] Preferably, the plasticizer is one or more combinations of dioctyl adipate, dimethyl phthalate, dioctyl phthalate, and diisodecyl phthalate; the stabilizer is one of a calcium zinc stabilizer and an organic tin stabilizer; and the lubricant is one of a polyethylene wax and an oxidized polyethylene wax.

[0010] Preferably, the preparation method of the modified additive comprises the following steps:

[0011] A. Take ethanol and deionized water in a reactor, place it at 40-50°C and stir for 10-15 minutes, add ammonium polyphosphate, OP-10 and ammonia water and stir to mix, then add tetraethyl orthosilicate and stir to react for 1-2 hours, cool to room temperature after the reaction is completed, filter, wash and dry to prepare silica-coated ammonium polyphosphate;

[0012] B. Dissolve γ-glycidyloxypropyltrimethoxysilane in a mixed solution of ethanol and deionized water to obtain an ethanol solution containing silane, ultrasonically disperse the silica-coated ammonium polyphosphate in anhydrous ethanol and place it in a reactor, adjust the pH value to 4-5 with dilute hydrochloric acid, then place it at 75-90° C., add the ethanol solution containing silane and stir to react for 5-8 hours, and after the reaction is completed, filter, wash and dry to prepare functionalized silica-coated ammonium polyphosphate;

[0013] C. Ultrasonic dispersion of graphene oxide in deionized water to obtain a dispersion, dissolving p-phenylenediamine in deionized water and adding the dispersion to the dispersion, ultrasonically mixing and reacting at 30-50° C. for 18-24 hours, filtering, washing and drying after the reaction to obtain amino-modified graphene oxide;

[0014] D. Put the amino-modified graphene oxide and the functionalized silica-coated ammonium polyphosphate in a reactor, add deionized water for ultrasonic dispersion, place at 35-50° C. for reaction for 18-24 hours, filter, wash and dry after the reaction to obtain a composite filler;

[0015] E. Take the composite filler and ultrasonically disperse it in deionized water, add amino boron nitride nanosheets and stir to mix, adjust the pH value of the system to 7-9 with a sodium carbonate solution with a mass fraction of 10-20%, then add carbodiimide and N-hydroxysuccinimide, stir and react for 3-5 hours, and after the reaction is completed, filter and dry to prepare the modified additive.

[0016] Preferably, in step D, the mass ratio of the aminated graphene oxide to the functionalized silica-coated ammonium polyphosphate is 1 to 3:1.

[0017] Preferably, in step E, the mass ratio of the composite filler to the amino boron nitride nanosheets is 0.75-1.2:1.

[0018] Preferably, the preparation method of the amination boron nitride nanosheets in step E comprises the following steps: putting boron nitride and urea in a ball mill, adding deionized water and steel balls for ball milling, centrifuging the reaction solution at 950-1100 r / min for 10-20 min after the ball milling, collecting the upper suspension and continuing to centrifuge at 4500-5000 r / min for 30-40 min, taking the lower precipitate and drying it to prepare the amination boron nitride nanosheets.

[0019] Preferably, the steel balls are steel balls with diameters of 2 mm, 5 mm, and 10 mm, which are mixed and added in a ratio of 4:2:1, the rotation speed of the ball mill is 750-900 r / min, and the ball milling time is 7-10 h.

[0020] Preferably, the preparation method of the hyperbranched flame retardant comprises the following steps:

[0021] (1) 1,5-naphthalenediamine is placed in a reactor, ethanol solvent is added and mixed evenly, terephthalaldehyde is dissolved in ethanol and added to the reactor, and the mixture is placed at 55-70° C. for condensation reflux reaction for 4-6 hours, and then DOPO is dissolved in ethanol and added to the reactor, and the mixture is heated to 75-90° C. for reaction for 5-7 hours. After the reaction is completed, the mixture is filtered, washed, and dried to prepare a DOPO derivative;

[0022] (2) A DOPO derivative, triethylamine and acetonitrile solvent are placed in a reactor, nitrogen is passed through the reactor and the reactor is placed at 0-4°C, an acetonitrile solution containing phosphorus oxychloride is added and the reaction is carried out for 1-2 hours, and then the reactor is moved to an oil bath at 45-60°C and refluxed under nitrogen for 18-24 hours. After the reaction is completed, the reactor is filtered, washed and dried to prepare a hyperbranched flame retardant.

[0023] Preferably, in step (2), the molar ratio of the DOPO derivative to phosphorus oxychloride is 1.5:1-1.2.

[0024] The method for preparing the outer sheath layer material of the pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable as described above comprises the following steps:

[0025] S1. Weigh each raw material by weight, take PVC resin, plasticizer and stabilizer and stir and mix them in a mixer, set the mixer temperature to 60-80°C, then add modifying additives, hyperbranched flame retardant and lubricant and continue to stir and mix, at this time, set the mixer temperature to 100-120°C, mix and extrude granulate to obtain masterbatch;

[0026] S2. Mix the masterbatch material and parts by weight of the polyurethane elastomer, put them into a twin-screw extruder for extrusion molding, and prepare an outer sheath layer material.

[0027] Beneficial effects of the present invention:

[0028] The invention first coats a layer of silicon dioxide particles on the surface of the ammonium polyphosphate flame retardant, and then uses the hydrolysis of the silicon hydroxyl group at one end of γ-glycidyloxypropyltrimethoxysilane to react with the hydroxyl group on the surface of the silicon dioxide-coated ammonium polyphosphate to prepare the functionalized silicon dioxide-coated ammonium polyphosphate containing epoxy groups. At the same time, the invention uses the amino group at one end of the antioxidant p-phenylenediamine to react with the epoxy group in the graphene oxide structure to prepare the amino graphene oxide, and then the amino graphene oxide is grafted with the functionalized silicon dioxide-coated polyphosphate. The amino The amino groups in the graphene oxide structure react with the epoxy groups in the functionalized silicon dioxide-coated polyphosphoric acid structure to prepare a composite filler. At the same time, the present invention uses boron nitride and urea as raw materials, synthesizes amino boron nitride nanosheets by ball milling, and reacts the composite filler with the amino boron nitride nanosheets under the participation of a carboxyl activator to prepare a modified additive, wherein the graphene oxide and the boron nitride nanosheets have excellent mechanical properties and can be used as thermal conductive fillers to improve the thermal conductivity of the material, thereby helping the material to dissipate heat. The addition of the modified additive of the present invention can give the material excellent mechanical properties, flame retardant properties, heat-resistant oxygen aging properties and heat resistance.

[0029] The invention uses DOPO, terephthalaldehyde and 1,5-naphthalenediamine as raw materials to synthesize a DOPO derivative. The 1,5-naphthalenediamine has good thermal stability and can release smoke and flame retardant gas that inhibit combustion at high temperature. Aldehyde groups at both ends of terephthalaldehyde react with one of the amino groups in the structure of 1,5-naphthalenediamine to generate N=C bonds. Then, the PH bond in the DOPO structure reacts with the N=C bond to prepare the DOPO derivative. Meanwhile, phosphorus oxychloride is used as a linker to cause a P-Cl group contained in the DOPO derivative to undergo a substitution reaction with the amino group in the structure of the DOPO derivative to prepare the hyperbranched flame retardant. The hyperbranched flame retardant can achieve excellent flame retardant effect and avoid affecting the mechanical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 It is a structural schematic diagram of the pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable of the present invention.

[0032] In the figure: 1-ground cable core, 2-power core, 21-conductor, 22-insulation layer, 3-signal control core, 31-signal cable core, 32-aluminum-plastic composite tape shielding layer, 33-copper wire braided shielding layer, 4-auxiliary power core, 5-filling layer, 6-tape layer, 7-copper wire braided total shielding layer, 8-outer sheath layer. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] like Figure 1As shown, a pressure-resistant, high-temperature-resistant and easy-to-dissipate heat dissipation new energy vehicle charging cable comprises, from inside to outside, a tape layer 6, a copper wire braided total shielding layer 7, and an outer sheath layer 8. The non-woven tape layer 6 is provided with three power cores 2, one ground cable core 1, two signal control cores 3, and two auxiliary power cores 4. The power core 2 comprises a conductor 21 and a cross-linked polyethylene insulation layer 22 extruded on the outer surface of the conductor. The signal control core 3 is provided with two signal cores 31. The outer surface of the signal core 31 is sequentially coated with an aluminum-plastic composite tape shielding layer 32 and a copper wire braided shielding layer 33. The gaps between the tape layer 6 and the three power cores 2, one ground cable core 1, two signal control cores 3, and two auxiliary power cores 4 are filled with a polypropylene filling rope filling layer 5.

[0035] Embodiment 1 A method for preparing a modified additive comprises the following steps:

[0036] A. Take 150 mL of ethanol and 50 mL of deionized water in a reactor, stir at 50 ° C for 10 min, add 50 g of ammonium polyphosphate, 1 g of OP-10 and 17 g of 25% ammonia water, stir and mix, then add 10 g of tetraethyl orthosilicate and stir to react for 2 h. After the reaction is completed, cool to room temperature, filter, wash and dry to prepare silica-coated ammonium polyphosphate;

[0037] B. Take 0.25g of γ-glycidyloxypropyltrimethoxysilane and dissolve it in a mixed solution of 10mL of ethanol and 10mL of deionized water to obtain an ethanol solution containing silane, ultrasonically disperse 2.5g of silica-coated ammonium polyphosphate in 200mL of anhydrous ethanol and place it in a reactor, adjust the pH value to 4 with dilute hydrochloric acid, then place it at 85°C, add the ethanol solution containing silane and stir to react for 7h, filter, wash and dry after the reaction is completed to prepare functionalized silica-coated ammonium polyphosphate;

[0038] C. Take 0.8 g of graphene oxide and ultrasonically disperse it in 100 mL of deionized water to obtain a dispersion, take 1.5 g of p-phenylenediamine and dissolve it in 100 mL of deionized water and add it to the dispersion, ultrasonically mix it and place it at 45° C. to react for 24 hours. After the reaction is completed, filter, wash and dry it to prepare amino-modified graphene oxide;

[0039] D. 1.5 g of amino-modified graphene oxide and 1 g of functionalized silica-coated ammonium polyphosphate were placed in a reactor, 180 mL of deionized water was added for ultrasonic dispersion, and the mixture was reacted at 50° C. for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried to prepare a composite filler.

[0040] E. Take 1.1g of the composite filler and ultrasonically disperse it in 200mL of deionized water, add 1g of amino boron nitride nanosheets and stir to mix, adjust the pH value of the system to 8 with a 15% mass fraction of sodium carbonate solution, then add 0.4g of carbodiimide and 0.5g of N-hydroxysuccinimide, stir and react for 4h, and after the reaction is completed, filter and dry to prepare a modified additive.

[0041] Among them, the preparation method of aminated boron nitride nanosheets includes the following steps: taking 2g of boron nitride and 100g of urea in a ball mill, adding 150mL of deionized water and steel balls with diameters of 2mm, 5mm and 10mm respectively (the number ratio is 4:2:1) for ball milling, the ball milling speed is 800r / min, the ball milling time is 8h, after the ball milling is completed, the reaction solution is placed at 1000r / min and centrifuged for 15min, the upper suspension is collected and continued to be centrifuged at 5000 / min for 30min, the lower precipitate is taken and dried to prepare aminated boron nitride nanosheets.

[0042] Embodiment 2 A method for preparing a hyperbranched flame retardant comprises the following steps:

[0043] (1) 15.8 g of 1,5-naphthalenediamine was placed in a reactor, 150 mL of ethanol solvent was added and mixed evenly, 6.7 g of terephthalaldehyde was dissolved in 50 mL of ethanol and added to the reactor, and the mixture was placed at 65° C. for condensation reflux reaction for 5 h, and 16 g of DOPO was dissolved in 100 mL of ethanol and added to the reactor, and the mixture was heated to 80° C. for reaction for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to prepare a DOPO derivative;

[0044] (2) 13.97 g of DOPO derivative, 3.34 g of triethylamine and 200 mL of acetonitrile solvent were placed in a reactor, nitrogen was passed through the reactor and the reaction was placed at 4°C, 40 mL of acetonitrile solution containing 1.82 g of phosphorus oxychloride was added and reacted for 2 h, then the mixture was moved to a 50°C oil bath and refluxed under nitrogen for 24 h. After the reaction was completed, the mixture was filtered, washed and dried to prepare a hyperbranched flame retardant.

[0045] Example 3 An outer sheath layer includes the following raw materials in parts by weight: 72 parts of PVC resin, 20 parts of polyurethane thermoplastic elastomer, 10 parts of the modified additive prepared in Example 1, 2 parts of the hyperbranched flame retardant prepared in Example 2, 5 parts of plasticizer dioctyl adipate, 4 parts of calcium zinc stabilizer, and 1 part of lubricant polyethylene wax.

[0046] The method for preparing the outer sheath layer material comprises the following steps:

[0047] S1. Weigh each raw material by weight, take PVC resin, plasticizer and stabilizer and stir and mix them in a mixer, set the mixer temperature to 75°C, then add modifying additives, hyperbranched flame retardant and lubricant and continue to stir and mix, at this time, set the mixer temperature to 110°C, mix and extrude granulate to obtain masterbatch;

[0048] S2. Mix the masterbatch material and parts by weight of the polyurethane elastomer, put them into a twin-screw extruder for extrusion molding, and prepare an outer sheath layer material.

[0049] Example 4 An outer sheath layer includes the following raw materials in parts by weight: 80 parts of PVC resin, 25 parts of polyurethane thermoplastic elastomer, 12 parts of the modified additive prepared in Example 1, 4 parts of the hyperbranched flame retardant prepared in Example 2, 7 parts of plasticizer dimethyl phthalate, 6 parts of organic tin stabilizer, and 2 parts of lubricant oxidized polyethylene wax.

[0050] The preparation method of the outer sheath layer material is the same as that of Example 3.

[0051] Example 5 An outer sheath layer includes the following raw materials in parts by weight: 88 parts of PVC resin, 30 parts of polyurethane thermoplastic elastomer, 15 parts of the modified additive prepared in Example 1, 5 parts of the hyperbranched flame retardant prepared in Example 2, 8 parts of plasticizer dioctyl adipate, 7 parts of calcium zinc stabilizer, and 3 parts of lubricant polyethylene wax.

[0052] The preparation method of the outer sheath layer material is the same as that of Example 3.

[0053] Comparative Example 1 A method for preparing a modified additive comprises the following steps:

[0054] 150 mL of ethanol and 50 mL of deionized water were placed in a reactor and stirred at 50° C. for 10 min. 50 g of ammonium polyphosphate, 1 g of OP-10 and 17 g of 25% ammonia water were added and stirred to mix. Then 10 g of tetraethyl orthosilicate was added and stirred to react for 2 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to prepare a modified additive.

[0055] Comparative Example 2 A method for preparing a modified additive comprises the following steps:

[0056] A. Take 150 mL of ethanol and 50 mL of deionized water in a reactor, stir at 50 ° C for 10 min, add 50 g of ammonium polyphosphate, 1 g of OP-10 and 17 g of 25% ammonia water, stir and mix, then add 10 g of tetraethyl orthosilicate and stir to react for 2 h. After the reaction is completed, cool to room temperature, filter, wash and dry to prepare silica-coated ammonium polyphosphate;

[0057] B. Take 0.25g of γ-glycidyloxypropyltrimethoxysilane and dissolve it in a mixed solution of 10mL of ethanol and 10mL of deionized water to obtain an ethanol solution containing silane, ultrasonically disperse 2.5g of silica-coated ammonium polyphosphate in 200mL of anhydrous ethanol and place it in a reactor, adjust the pH value to 4 with dilute hydrochloric acid, then place it at 85°C, add the ethanol solution containing silane and stir to react for 7h, filter, wash and dry after the reaction is completed to prepare functionalized silica-coated ammonium polyphosphate;

[0058] C. Take 0.8 g of graphene oxide and ultrasonically disperse it in 100 mL of deionized water to obtain a dispersion, take 1.5 g of p-phenylenediamine and dissolve it in 100 mL of deionized water and add it to the dispersion, ultrasonically mix it and place it at 45° C. to react for 24 hours. After the reaction is completed, filter, wash and dry it to prepare amino-modified graphene oxide;

[0059] D. Take 1.5g of amino-modified graphene oxide and 1g of functionalized silica-coated ammonium polyphosphate in a reactor, add 180mL of deionized water for ultrasonic dispersion, and place at 50°C for reaction for 24h. After the reaction is completed, filter, wash and dry to prepare a modified additive.

[0060] Comparative Example 3: An outer sheath layer includes the following raw materials in parts by weight: 88 parts of PVC resin, 30 parts of polyurethane thermoplastic elastomer, 15 parts of the modified additive prepared in Comparative Example 1, 5 parts of the hyperbranched flame retardant prepared in Example 2, 8 parts of plasticizer dioctyl adipate, 7 parts of calcium zinc stabilizer, and 3 parts of lubricant polyethylene wax.

[0061] The preparation method of the outer sheath layer material is the same as that of Example 3.

[0062] Comparative Example 4: An outer sheath layer includes the following raw materials in parts by weight: 88 parts of PVC resin, 30 parts of polyurethane thermoplastic elastomer, 15 parts of the modified additive prepared in Comparative Example 2, 5 parts of the hyperbranched flame retardant prepared in Example 2, 8 parts of plasticizer dioctyl adipate, 7 parts of calcium zinc stabilizer, and 3 parts of lubricant polyethylene wax.

[0063] The preparation method of the outer sheath layer material is the same as that of Example 3.

[0064] Comparative Example 5: An outer sheath layer includes the following raw materials in parts by weight: 88 parts of PVC resin, 30 parts of polyurethane thermoplastic elastomer, 15 parts of the modified additive prepared in Example 1, 8 parts of plasticizer dioctyl adipate, 7 parts of calcium zinc stabilizer, and 3 parts of lubricant polyethylene wax.

[0065] The preparation method of the outer sheath layer material is the same as that of Example 3.

[0066] Performance Testing

[0067] (1) Flame retardant performance test: The sheath layer materials prepared in Examples 3-5 and Comparative Examples 3-5 were made into test samples with a specification of 100 mm×6.5 mm×3 mm. The flame retardant performance of the samples was evaluated by referring to the limiting oxygen index of the test samples in accordance with GB / T 2406.2-2009. Generally speaking, the larger the limiting oxygen index, the better the flame retardant performance, and vice versa. The data results are shown in Table 1.

[0068] Table 1 Test results of flame retardant properties of samples

[0069]

[0070]

[0071] It can be seen from the data in Table 1 that the sheath layer materials prepared in Examples 3-5 of the present invention have a high limiting oxygen index and good flame retardancy. In Comparative Example 5, no hyperbranched flame retardant was added, and the flame retardancy measured was significantly lower than that of Examples 3-5.

[0072] (2) Mechanical property test: The sheath layer materials prepared in Examples 3-5 and Comparative Examples 3-5 were subjected to a tensile property test using a universal mechanical testing machine in accordance with GB / T 1040.2-2022, and the change rates of tensile strength and elongation at break were tested after aging at 110°C for 168 h. The size of the sample strip was 100 mm × 5 mm × 3.5 mm. The impact strength was tested in accordance with GB / T1843-2008. The size of the sample strip was 80 mm × 10 mm × 4 mm. The tear strength was tested in accordance with GB / T 529-2008. The data results are shown in Table 2.

[0073] (3) Heat resistance test: The sheath layer materials prepared in Examples 3-5 and Comparative Examples 3-5 were placed in a TGA-103 thermogravimetric analyzer, respectively. Under nitrogen protection, the temperature was increased from room temperature to 800°C at a rate of 5°C / min, and the initial decomposition temperature of the material was recorded. The thermal conductivity was tested in accordance with GB / T 3399-1982, and the data results are shown in Table 2.

[0074] Table 2 Test results of mechanical properties and heat resistance of samples

[0075]

[0076]

[0077] It can be seen from the data in Table 2 that the sheath layer materials prepared in Examples 3-5 of the present invention all have the characteristics of high tensile strength, strong compressive resistance, good heat resistance, and not easy to break. Among them, in Comparative Example 3, the modified additive component is not grafted with amino-modified graphene oxide and boron nitride nanosheets, and its measured mechanical properties, tensile strength change rate, elongation at break change rate, initial decomposition temperature and thermal conductivity are significantly lower than those of Examples 3-5. In Comparative Example 4, the modified additive component is not grafted with boron nitride nanosheets, and its measured mechanical properties, initial decomposition temperature and thermal conductivity are lower than those of Examples 3-5, indicating that the addition of amino-modified graphene oxide grafted with p-phenylenediamine antioxidant can improve the thermal oxygen aging resistance of the material, and graphene oxide and boron nitride nanosheets give the sheath layer material excellent mechanical properties and heat resistance to a certain extent.

[0078] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0079] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A pressure-resistant, high-temperature-resistant and easy-to-dissipate heat dissipation new energy vehicle charging cable, characterized in that: The charging cable includes a tape layer, a copper wire braided overall shielding layer, and an outer sheath layer from the inside to the outside. Three power cores, one ground cable core, two signal control cores, and two auxiliary power cores are arranged in the tape layer. The power core includes a conductor and an insulating layer extruded on the outer surface of the conductor. The signal control core is provided with two signal cores. The outer surface of the signal core is sequentially coated with an aluminum-plastic composite tape shielding layer and a copper wire braided shielding layer. The gaps between the tape layer and the three power cores, one ground cable core, two signal control cores, and two auxiliary power cores are filled with a filling layer. The outer sheath layer comprises the following raw materials in parts by weight: 70-90 parts of PVC resin, 20-30 parts of polyurethane thermoplastic elastomer, 10-15 parts of modified additives, 2-5 parts of hyperbranched flame retardant, 5-10 parts of plasticizer, 4-7 parts of stabilizer, and 1-3 parts of lubricant; The modified additive is prepared by gamma-glycidyloxypropyltrimethoxysilane treated silicon dioxide coated with ammonium polyphosphate grafted with amination graphene oxide and then further grafted with amination boron nitride nanosheets; the hyperbranched flame retardant is prepared by using DOPO, terephthalaldehyde and 1,5-naphthalenediamine as raw materials to synthesize DOPO derivatives and then using phosphorus oxychloride as a linker.

2. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 1 is characterized in that: The plasticizer is one or more combinations of dioctyl adipate, dimethyl phthalate, dioctyl phthalate, and diisodecyl phthalate; the stabilizer is one of a calcium zinc stabilizer and an organic tin stabilizer; and the lubricant is one of a polyethylene wax and an oxidized polyethylene wax.

3. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 1, characterized in that: The preparation method of the modified additive comprises the following steps: A. Take ethanol and deionized water in a reactor, place it at 40-50°C and stir for 10-15 minutes, add ammonium polyphosphate, OP-10 and ammonia water and stir to mix, then add tetraethyl orthosilicate and stir to react for 1-2 hours, cool to room temperature after the reaction is completed, filter, wash and dry to prepare silica-coated ammonium polyphosphate; B. Dissolve γ-glycidyloxypropyltrimethoxysilane in a mixed solution of ethanol and deionized water to obtain an ethanol solution containing silane, ultrasonically disperse the silica-coated ammonium polyphosphate in anhydrous ethanol and place it in a reactor, adjust the pH value to 4-5 with dilute hydrochloric acid, then place it at 75-90° C., add the ethanol solution containing silane and stir to react for 5-8 hours, and after the reaction is completed, filter, wash and dry to prepare functionalized silica-coated ammonium polyphosphate; C. Ultrasonic dispersion of graphene oxide in deionized water to obtain a dispersion, dissolving p-phenylenediamine in deionized water and adding the dispersion to the dispersion, ultrasonically mixing and reacting at 30-50° C. for 18-24 hours, filtering, washing and drying after the reaction to obtain amino-modified graphene oxide; D. Put the amino-modified graphene oxide and the functionalized silica-coated ammonium polyphosphate in a reactor, add deionized water for ultrasonic dispersion, place at 35-50° C. for reaction for 18-24 hours, filter, wash and dry after the reaction to obtain a composite filler; E. Take the composite filler and ultrasonically disperse it in deionized water, add amino boron nitride nanosheets and stir to mix, adjust the pH value of the system to 7-9 with a sodium carbonate solution with a mass fraction of 10-20%, then add carbodiimide and N-hydroxysuccinimide, stir and react for 3-5 hours, and after the reaction is completed, filter and dry to prepare the modified additive.

4. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 3 is characterized in that: In the step D, the mass ratio of the aminated graphene oxide to the functionalized silica-coated ammonium polyphosphate is 1 to 3:

1.

5. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 3 is characterized in that: In the step E, the mass ratio of the composite filler to the amino boron nitride nanosheets is 0.75-1.2:

1.

6. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 3, characterized in that: The preparation method of the amino boron nitride nanosheets in step E comprises the following steps: taking boron nitride and urea into a ball mill, adding deionized water and steel balls for ball milling, centrifuging the reaction solution at 950-1100 r / min for 10-20 min after the ball milling, collecting the upper suspension and continuing to centrifuge at 4500-5000 r / min for 30-40 min, taking the lower precipitate and drying it to prepare the amino boron nitride nanosheets.

7. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 6, characterized in that: The steel balls are 2mm, 5mm and 10mm in diameter, which are mixed and added in a ratio of 4:2:

1. The rotation speed of the ball mill is 750-900r / min, and the ball milling time is 7-10h.

8. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 1, characterized in that: The preparation method of the hyperbranched flame retardant comprises the following steps: (1) 1,5-naphthalenediamine is placed in a reactor, ethanol solvent is added and mixed evenly, terephthalaldehyde is dissolved in ethanol and added to the reactor, and the mixture is placed at 55-70° C. for condensation reflux reaction for 4-6 hours, and then DOPO is dissolved in ethanol and added to the reactor, and the mixture is heated to 75-90° C. for reaction for 5-7 hours. After the reaction is completed, the mixture is filtered, washed, and dried to prepare a DOPO derivative; (2) A DOPO derivative, triethylamine and acetonitrile solvent are placed in a reactor, nitrogen is passed through the reactor and the reactor is placed at 0-4°C, an acetonitrile solution containing phosphorus oxychloride is added and the reaction is carried out for 1-2 hours, and then the reactor is moved to an oil bath at 45-60°C and refluxed under nitrogen for 18-24 hours. After the reaction is completed, the reactor is filtered, washed and dried to prepare a hyperbranched flame retardant.

9. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 8, characterized in that: In the step (2), the molar ratio of the DOPO derivative to phosphorus oxychloride is 1.5:1-1.

2.

10. The pressure-resistant, high-temperature-resistant and heat-dissipating new energy vehicle charging cable according to claim 1, characterized in that: The preparation method of the outer sheath layer material comprises the following steps: S1. Weigh each raw material by weight, take PVC resin, plasticizer and stabilizer and stir and mix them in a mixer, set the mixer temperature to 60-80°C, then add modifying additives, hyperbranched flame retardant and lubricant and continue to stir and mix, at this time, set the mixer temperature to 100-120°C, mix and extrude granulate to obtain masterbatch; S2. Mix the masterbatch material and parts by weight of the polyurethane elastomer, put them into a twin-screw extruder for extrusion molding, and prepare an outer sheath layer material.

Citation Information

Patent Citations

  • Halogen-free DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide)-based hyperbranched structure phosphate flame retardant and preparation method thereof

    CN107501566A

  • Crosslinked polyethylene insulated flame-retardant polyvinyl chloride sheath variable frequency cable

    CN114864165A

  • Temperature-resistant copper conductor cable for computer and preparation method thereof

    CN117133506A

  • Thermal grease based on hyperbranched olefinic fluid

    US20170226396A1

  • PVC cable material and preparation method therefor

    WO2021129216A1

Cited By

  • Cable for direct current charging system of new energy vehicle

    CN120072396A

  • A cable for DC charging system of new energy vehicles

    CN120072396B

  • Fireproof cable material and preparation method thereof

    CN120623610A

  • Cable for direct-current charging system of new energy vehicle

    WO2026194077A1